Analisis Pengaruh Bayangan Terhadap Daya Keluaran Yang Dihasilkan Oleh Pembangkit Listrik Tenaga Surya - Rohana Rohana; Muhammad Fitra Zambak; Ihsanurrizqie Indra Siregar (Schrodinger Jurnal Ilmiah Mahasiswa Pendidikan Fisika, 2023)
In using PLTS, of course there are various obstacles that can cause the quantity of power produced to decrease. There are several factors that can cause a reduced power output from the solar power plant, one of which is the shadow. In this study, the PLTS output was calculated when it was covered with shadows and not covered with shadows, which was simulated using the Helioscope software. The simulation technique is carried out by covering the PLTS with the shadow produced by the building, where the resulting shadow is for shelter up to 25%, 50% and 75%. The load used in the simulation is the total load in the PT. KAI Medan Branch. The results of this study indicate that when the PLTS condition is covered by a shadow of 25%, the effective PLTS is used with a capacity of 453.4 kWp and the resulting output power is 534 MWh. In the shading condition of 50% effective PLTS that can be used is 300.2 kWp with an output power of 356.5 MWh and when conditions are 75% effective PLTS is only 176.1 kWp and an output power of 481 MWh.